EXPLORING BARRIERS AND OPPORTUNITIES IN PRECONCEPTION EDUCATION: PERSPECTIVES FROM BRIDES, HEALTH WORKERS, AND RELIGIOUS OFFICIALS - Ayudia, Fanny; Erwani, Erwani; Ilmaskal, Radian (IAKMI South Tangerang Branch, 2024)
Background: Maternal and child health issues remain significant in Indonesia, partly due to limited understanding among brides regarding preconception health and healthy pregnancy planning. Method: We utilized a qualitative phenomenological approach. Participants included five brides, three marriage officials from the Religious Official (RO), and three health workers at the public health center (PHC). Data were collected through in-depth interviews, observations, and documentation, then analyzed using the Braun and Clarke method. Results: Findings reveal that brides have limited knowledge of preconception health, while health workers and RO officers face constraints in providing preconception education due to time and resource limitations. Conclusion: This study highlights the urgent need for more comprehensive and effective preconception education to support healthy pregnancy planning.